Continuous monitoring of vital signs with the Everion biosensor on the surgical ward: a clinical validation study. (3rd December 2021) - Haveman, Marjolein E.; van Melzen, Rianne; Schuurmann, Richte C.L.; El Moumni, Mostafa; Hermens, Hermie J.; Tabak, Monique; de Vries, Jean-Paul P.M.
ABSTRACT: Background: Wearable sensors enable continuous vital sign monitoring, although information about their performance on nursing wards is scarce. Vital signs measured by telemonitoring and nurse measurements on a surgical ward were compared to assess validity and reliability. Methods: In a prospective observational study, surgical patients wore a wearable sensor (Everion, Biovotion AG, Zürich, Switzerland) that continuously measured heart rate (HR), respiratory rate (RR), oxygen saturation (SpO2 ), and temperature during their admittance on the ward. Validity was evaluated using repeated-measures correlation and reliability using Bland-Altman plots, mean difference, and 95% limits of agreement (LoA). Results: Validity analyses of 19 patients (median age, 68; interquartile range, 62.5–72.5 years) showed a moderate relationship between telemonitoring and nurse measurements for HR ( r = 0.53; 95% confidence interval, 0.44–0.61) and a poor relationship for RR, SpO2, and temperature. Reliability analyses showed that Everion measured HR close to nurse measurements (mean difference, 1 bpm; LoA, −16.7 to 18.7 bpm). Everion overestimated RR at higher values, whereas SpO2 and temperature were underestimated. Conclusions: A moderate relationship was determined between Everion and nurse measurements at a surgical ward in this study. Validity and reliability of telemonitoring should also be assessed with gold standard devices in future clinical trials.